Arvot luonnossa - Rolston, Holmes, 1932-2025, author; Gaudeamus, publisher (Colorado State University. Libraries, 1997)
Nature is examined as a carrier of values. Ten areas of values are recognized: (1) economic value, (2) life support value, (3) recreational value, (4) scientific value, (5) aesthetic value, (6) life value, (7) diversity and unity values, (8) stability and spontaneity values, (9) dialectical value, and (10) sacramental value. Each is analyzed and illustrated with particular reference to the objective precursors of value described by natural science.
Values in nature
Text in Finnish.
Keywords: wilderness; value in nature; valuation; valuational education